Recrutamento da Stress inducible protein (STI-1) desempenha função protetora na resposta ao estresse cardíaco - Iara Pastor Nogueira (2020)
STI-1 (Stress inducible protein) is an important co-chaperone of Hsp70/Hsp90 machinery that plays a key role in protein maturation and intracellular cascades initiation. However, its role at heart physiology still unknown. This project becomes relevant when Western Blot assay of human heart samples from heart failure patients showed a reduction in STI-1 levels of expression, when compared to samples from control patients. Therefore, animal models that present a lower level of STI-1 are important to comprehend the role of this chaperone in the physiopathology of heart failure.This way, the main objective of this project is to investigate the impact of reduced STI-1 protein expression on heart during physiological development and in front of a cardiac stress induced by adrenergic agonist, isoproterenol. In this project were used two models of genetic engineering mice, the STI-1+/- e o ∆TPR, with global reduction of STI-1 expression. Initially, body development, cardiac structure and function, were assessed for Wild-type (C57BL) and genetically engineered mice with reduced STI-1 levels, aging from 8-12 weeks. Afterwards two groups were treated for 7 days, one with saline and other with isoproterenol intraperitoneally (20mg/Kg/day). Mice were euthanized after proceeding an echocardiogram exam, and hearts weighted and used in histology for morphometric quantification; in cardiomyocyte isolation for cell imaging and cellular area analysis; in protein extraction for Western Blot analysis; and RNA extraction for qPCR techniques. After confirmation that not only human hearts, but also cardiomyocytes from adult mice express STI-1 protein, was noticed that all mice lines presented similar body and cardiac development, from a molecular, structural and functional aspect. After the treatment, both WT, STI-1KO+/-, and ∆TPR mice treated with isoproterenol showed an increase in heart weight by Tibia length ratio, when compared to their controls. Nevertheless, only isoproterenol stimulated wild-type cardiomyocytes presented cellular hypertrophy, with increased diameter. Through morphometric analysis, a significant increase in stromal tissue and inflammatory cells percentage in STI-1KO+/- and ∆TPR animals stimulated with isoproterenol was observed, justifying the gain in heart weight, without concomitant cellular hypertrophy in this model. At the same time, a decrease in cardiomyocytes was noticed with concomitant major presence of activated caspase in the tissue and no difference in the levels of Heat shock protein machinery and in ER stress markers. A Western Blot assay showed a significant increase of STI-1 level of expression after treatment in WT Animals; indicating that Isoproterenol in an initial moment recruits STI-1 machinery. Equivalents findings were seen in mice subjected to transverse aortic constriction, suggesting this effect can be extended to different cardiac stress models. However, this increased at STI-1 was not significant in STI-1KO+/- and ∆TPR animals. Therefore, combining these results can be concluded that, the reduction in STI-1 protein expression do not affect the physiological hypertrophy from cardiac development, although it compromises the cardiac pathological process. Also hearts with an impaired response from the STI-1 machinery, are more susceptible to develop cardiac injury induced by a major adrenergic stimuli. The project results indicate an important protector role from STI-1 in hearts in front of stress conditions.